HLA-DMA*0103 and HLA-DMB*0104 alleles as novel prognostic factors in rheumatoid arthritis. Issue 12 (16th November 2004) - Morel, J; Roch-Bras, F; Molinari, N; Sany, J; Eliaou, J F; Combe, B
Abstract : Objective: To evaluate HLA-DM alleles as markers for disease severity in rheumatoid arthritis (RA). Methods: Two distinct cohorts of patients with RA were oligotyped for HLA-DB1 and HLA-DM genes using PCR amplified genomic DNA with sequence specific oligonucleotide probes. Cohort 1 comprised 199 unselected patients with RA (mean (SD) age 45.5 (13.5) years; disease duration 11.9(8.8) years), whose disease severity was assessed using Larsen score on hand and foot radiographs. Cohort 2 comprised 95 patients with severe RA and 70 patients with benign RA according to the Larsen method. Results: In cohort 1, after stratification according to DRB1 genotypes, patients positive for HLA-DMA*0103 and negative for HLA-DRB1*04 tended to have greater articular damage on hands and wrists (p = 0.07 by Mann-Whitney U test) and reached statistical significance for the Larsen score per year (p = 0.05). This association between HLA-DMA*0103 and articular damage was especially observed in patients with HLA-DRB1*01. Similarly, HLA-DMB*0104 positive patients had higher Larsen score on hands and wrists (p = 0.02). This association was even stronger in DRB1*04 positive patients (p = 0.005). In cohort 2, HLA-DMA*0103 was associated with severe RA in patients negative for HLA-DRB1*04 (OD = 5.4; p = 0.014). HLA-DMB*0104 allele frequency tended to be higher in patients with severe RA but without reaching significance. Conclusion: This is the first study evaluating the role of HLA-DM genes in the severity of RA. Our results suggest that HLA-DMA*0103 and HLA-DMB*0104 alleles may represent new genetic markers of RA severity. The HLA-DMA*0103 allele tends to be associated with patients with RA negative for DRB1*04 and could predict a more severe form of disease especially in HLA-DRB1*01 positive patients. The HLA-DMB*0104 allele could have an additive effect in HLA-DRB1*04 patients. Combined determination of HLA-DM and HLA-DRB1 alleles could facilitate identification of patients likely to have a poor disease course.